Respuesta :

Answer:

(3,9)

Step-by-step explanation:

This is a quadratic equation.

A quadratic in standard form is [tex]y=ax^2+bx+c[/tex].

If we compare [tex]y=ax^2+bx+c[/tex] to [tex]y=6x-x^2[/tex], we see there [tex]c=0,b=6,a=-1[/tex].

Now to find the vertex, we first find the x-coordinate of the vertex which is:

[tex]\frac{-b}{2a}[/tex].

So now plug in our values:

[tex]\frac{-6}{2(-1)}=\frac{-6}{-2}=3[/tex]

So the corresponding y-coordinate can be found by the equation that relates x to y:  [tex]y=6x-x^2[/tex].

So we are plugging in 3 where we see x:  [tex]y=6(3)-3^2=18-9=9[/tex].

So the vertex is (3,9).